Aplikasi Drone Penabur Benih Jagung Sebagai Pertanian Berkelanjutan - Mulyana; Handoko Riyanto; Erry Yulian Triblas Adesta; Riza Muhida; Harjono Saputro; Muhammad Riza; Tia Tanjung (BKS-TM Indonesia, 2025)
Corn cultivation in Indonesia continues to face challenges related to productivity and operational efficiency. According to data from the Central Bureau of Statistics, in 2023, the harvested area of corn was approximately 2.48 million hectares, with total production of 14.77 million tons, representing a decline of more than 10% compared to the previous year. This decline indicates that conventional planting methods have not fully met the demands for efficiency and sustainability in modern agricultural systems. One emerging technological innovation is the utilization of Unmanned Aerial Vehicles (UAVs) in agricultural practices. UAV technology has previously been applied for pest control and shows strong potential for expansion into fertilization and seed distribution. This study aims to design and evaluate a UAV-based system for efficient and accurate corn seed broadcasting. The research methods include hardware design, integration of an automated control software system, and field testing to assess the technology's reliability and performance. The results show that the UAV system can distribute corn seeds with an accuracy of approximately 92–96%, higher than that of conventional methods. In addition, planting efficiency significantly improved, with one hectare of land being planted within 35–45 minutes compared to 18–25 hours using manual methods. The implementation of UAV technology also reduces labor requirements, improves operational efficiency, and supports the adoption of more modern and sustainable agricultural practices.